Utilizing Folklore to Enhance English Oral Skills of Junior High School Students - Binsasi, Mario Valderamo Aliandro; Bouk, Edmundus; Pale, Erlinda Sonya; Sulaiman, Eugelin; Semiun, Thresia Trivict (Universitas Nurul Jadid, 2025)
This research aimed to enhance the speaking skills of the third-grade students at SMPN Kota Baru Kefamenanu through the use of folklore. The study employed a pre-experimental design, consisting of three stages: pre-test, treatment, and post-test. Initial findings from the pre-test showed that students had an average speaking skill score of 53.60%, classified as